Unveiling the Essence of Performance Testing: A Comprehensive Review (Journal of Science & Technology, 2022)
Performance testing is a pivotal component of the software development lifecycle, ensuring that applications meet the demands of users in terms of speed, responsiveness, scalability, and reliability. This review article delves into the multifaceted world of performance testing, exploring its significance, key metrics, testing strategies, and the evolving landscape of performance testing tools.